2018
DOI: 10.1080/09638237.2018.1466039
|View full text |Cite
|
Sign up to set email alerts
|

Four decades following the Khmer rouge: sociodemographic factors impacting depression, anxiety and PTSD in Cambodia

Abstract: These findings can inform Cambodian mental health policies and development strategies, especially targeting the most vulnerable groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 37 publications
4
25
5
Order By: Relevance
“…These rates are significantly higher than the general Cambodian population and are higher than found in previous studies of FEWs. A recent study of the general Cambodian population found the prevalence of depression to be 27.4% [35], much lower than the 67% found in the current study. A study of female street workers in Miami, USA found the prevalence of depression to be 53% [36], still much lower than found in the current study where rates are more comparable to a clinical sample found in China which found 72% prevalence of depression [37].…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…These rates are significantly higher than the general Cambodian population and are higher than found in previous studies of FEWs. A recent study of the general Cambodian population found the prevalence of depression to be 27.4% [35], much lower than the 67% found in the current study. A study of female street workers in Miami, USA found the prevalence of depression to be 53% [36], still much lower than found in the current study where rates are more comparable to a clinical sample found in China which found 72% prevalence of depression [37].…”
Section: Discussioncontrasting
confidence: 92%
“…The current study's finding of anxiety level of 61% among FEWs is much higher than found (a) among the Cambodian general population (16.7%, [35]) (b) among sex worker samples in Miami (37.4%; [36]) and (c) compared to sex worker in India (42%; [38]). This is likely due to high levels of risk and stress associated with Cambodian FEWs' lives.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Cambodia is home to largest youth and adolescent population in the South East Asia region, with approximately two third of population between age of 15-24 and nearly a quarter between 10-19 year old [14]. Previous studies suggested a high prevalence of mental health-related problems among both Cambodian children and adults [15][16][17]. In a nationally representative study, 8.2% of households with children reported one or more children were having school problems, 11.5% reported child aggressive behavior, and 4.9% reported children were experiencing other mental health-related problems [15].…”
Section: Introductionmentioning
confidence: 99%
“…Cambodia provides a unique context in which to investigate trauma development. From 1975 to 1979, Cambodia experienced genocide at the hands of the KR, with losses estimated between 1.5 and 3 million people (Seponski, Lahar, Khann, Kao, & Schunert, 2018). Following the genocide, the country entered into a period of civil war and was under the direction of several unstable regimes before entering into a period of relative political stability.…”
mentioning
confidence: 99%